Effect of Implementing the E-Filing System Regarding Taxpayer Compliance with Tax Socialization and Internet Understanding as a Moderating Variable in DJP Regional Office North Sumatra I - Ega Arsita; Agus Tripriyono (International Forum of Researchers and Lecturers, 2022)
The study aims to analyze the influence of Application System E-Filing against obedience must tax with socialization taxation and understanding the internet as variable moderation. research data was obtained from a questionnaire (primary) distributed to Must North Sumatra I Medan DJP Tax with the use method of convenience sampling. Population study is must personal Tax North Sumatra I Medan DJP. Sample used in research this as many as 50 respondents. The questionnaire was tested using a validity test and a reliability test before the research. Test assumptions classic used are the normality test, multicollinearity test, heteroscedasticity test, and linearity test. The hypothesis test used is simple linear regression and Moderated Regression Analysis. Research results show that implementation of system E-Filing has an effect significant to obedience must tax, socialization taxation strengthens the application of system e-filing to obedience must tax, and internet understanding strengthens the application of system E-Filing against obedience must tax.